2002
DOI: 10.2320/matertrans.43.2468
|View full text |Cite
|
Sign up to set email alerts
|

Local Bonding States of Titanium and Germanium-doped Tetragonal Zirconia Polycrystal and Their Correlation to High Temperature Ductility

Abstract: The chemical bonding states of GeO 2 and/or TiO 2 -doped tetragonal zirconia polycrystal (TZP) are calculated by a first principle molecular orbital method using model clusters. It is clarified that Ge 4+ and Ti 4+ ions, which are substituted into a lattice of TZP, have a high covalent bond with oxygen ions rather than Zr-O bond. Covalency of TZP is more increased by solution of germanium ions than that of titanium ones. In superplastic deformation of TZP, an addition of GeO 2 or TiO 2 enhances tensile ductili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…(2) The addition of dopants, which can suppress the generation of flat cavities even when the stress applied to the specimen is high, improves the elongation as well. The former idea coincides with the results given by Kim et al,24) while the latter coincides with that shown by Kuwabara et al, 23) though qualitatively. In conclusion, it is most probable that whether the generation of flat cavities is easy to occur or not is a crucial phenomenon to determine the elongation to fracture of superplastic ceramics.…”
Section: Flat Cavitiessupporting
confidence: 82%
See 3 more Smart Citations
“…(2) The addition of dopants, which can suppress the generation of flat cavities even when the stress applied to the specimen is high, improves the elongation as well. The former idea coincides with the results given by Kim et al,24) while the latter coincides with that shown by Kuwabara et al, 23) though qualitatively. In conclusion, it is most probable that whether the generation of flat cavities is easy to occur or not is a crucial phenomenon to determine the elongation to fracture of superplastic ceramics.…”
Section: Flat Cavitiessupporting
confidence: 82%
“…Recently, it has been reported [20][21][22] that an addition of dopants which segregate and alter the chemical bonding state at and nearby grain boundaries sensitively changes the elongations to fracture of TZP. More recently, Kuwabara et al 23) have shown that the elongation to fracture of TZP has a close relation with covalency at and nearby grain boundaries; an addition of dopants, which enhances the covalency, improves the elongation considerably. They 23) have explained that the enhancement of the grain boundary covalency makes grain boundary cohesion stronger and suppresses intergranular failure accordingly.…”
Section: Flat Cavitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11] Recent studies have pointed out that covalent bonding states nearby grain boundaries correlate with the tensile ductility of TZP and Al 2 O 3 . [12][13][14] Further analyses to the grain boundaries are indispensable to fully understand the tensile ductility of TZP.…”
Section: Introductionmentioning
confidence: 99%